SISTEM INFORMASI PELAYANAN PASIEN BERBASIS WEB PADA KLINIK TANJUNG LUMUT: Data Processing;Patient;System;Website. - Handayani, Yuli; -, Mulyadi (JURNAL AKADEMIKA, 2020)
Tanjung Lumut Clinic is an institution engaged in health services. Health services in this clinic for the community still seem not optimal when compared to technological advances, the patient's need for better services is felt to be increasingly important in order to achieve more effective and efficient services. The patient service system currently running at the Tanjung Lumut Clinic is still manual, still using paper media to support their work activities, the use of paper media is not optimal, the obstacles faced at the Tanjung Lumut Clinic are when registering patients, employees must record patient data visits every day into the daily visit ledger and if there are patients who come and do not bring their medical card, the employee must look for patient data, a more effective computerized system is needed to support better service to the community, besides being very useful to facilitate the work of employees in do its job.